CD20+ and CD204+ exhibit distinct prognostic associations in thymic epithelial tumors - Chen, Qinyang; Zhang, Jian; Feng, Jianwei; Chen, Chaowen; Su, Chuan; Yao, Wenxiu (Frontiers in Oncology, 2025)
IntroductionThymic epithelial tumors (TETs), encompassing thymomas and thymic carcinomas, are rare malignancies originating from thymic epithelial cells. This study aimed to characterize tumor-infiltrating immune cells (TIIC) within the tumor microenvironment (TME) and evaluate their prognostic significance in TETs.MethodsWe retrospectively analyzed 125 patients with surgically resected TETs (2009-2021). Immunohistochemical staining of tumor specimens was performed to assess TIIC distribution, with significant associations between immune markers and survival outcomes evaluated using Cox regression. ResultsAmong the analyzed markers, CD20, CD204, CD206, and CD47 emerged as potential predictors for disease-free survival (DFS), while CD20 and CD204 showed prognostic relevance for overall survival (OS). Specifically, stromal CD20+ TIIC density was independently associated with prolonged DFS(HR=4.74, 95% CI(1.673-13.434), P=0.003) and OS (HR=5.086, 95% CI(1.391-18.594), P=0.014), whereas elevated CD204+ TIIC infiltration correlated with reduced DFS(HR=0.154, 95% CI(0.043-0.547), P=0.004) and OS(HR=0.169, 95% CI(0.056-0.607), P=0.002).ConclusionThese findings suggest that targeting M2 macrophage-driven immunosuppression may enhance therapeutic efficacy in TETs.